Identifikasi Dan Hitung Jumlah Bakteri Pada Telapak Tangan Penjual Gorengan - Anita, Anita; Muawanah, Muawanah; Fatmawati, Andi; Rahmawati, Rahmawati; Faisal, Faisal (Lontara Journal of Health Science and Technology, 2023)
The palm is the part of the body that is most often used daily to carry out various activities, which makes hands very easily contaminated by bacteria. This causes the palm of the hand can act as a medium for transmission of various types of diseases. This study aims to identify and count the number of bacteria on the palms of fried food sellers. This research technique was carried out by laboratory observation with the object of research being the palms of 10 fried food sellers in Rappocini District, Makassar City. Based on the results of research that has been carried out from 10 samples, it has been identified microscopically the form of gram-negative bacilli is red and clustered and macroscopic identification shows the shape of bacterial colonies is round, jagged with small to large sizes, while the results of calculating the number of bacteria for all samples obtained the number of bacteria in large numbers (TBUD). It can be concluded that the palms of fried food sellers in Rappocini District, Makassar City are positive for gram-negative bacilli with an amount that cannot be counted (TBUD).